2020
DOI: 10.2174/1745017902016010059
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression Among Women Living with HIV: Prevalence and Correlations

Abstract: Introduction: It has been found that HIV positive women are becoming increasingly affected by various illnesses, including Common Mental Disorders (CMDs) such as depression. Such comorbidity escalates the disease progression to the severe stage and commonly hinders treatment adherence. This study determined the prevalence of anxiety and depression amidst women living with HIV. Methods: Based on a cross-sectional and facility-based study, 357 HIV positive women we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
55
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 39 publications
9
55
1
6
Order By: Relevance
“…34 These prevalence rates are far less than 49.5% found among HIV-positive pregnant women but slightly higher than 21.2% found among HIV-negative pregnant women in this study. Studies from other African countries among HIV-positive pregnant women by Ngocho et al 32 and Yousuf et al 25 conducted before the COVID-19 found a prevalence of depression and anxiety (25% and 24.3%) and (32.5% and 28.9%) in Tanzania and Ethiopia respectively. The prevalence of depression and anxiety found in these studies was far less than in our study conducted during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…34 These prevalence rates are far less than 49.5% found among HIV-positive pregnant women but slightly higher than 21.2% found among HIV-negative pregnant women in this study. Studies from other African countries among HIV-positive pregnant women by Ngocho et al 32 and Yousuf et al 25 conducted before the COVID-19 found a prevalence of depression and anxiety (25% and 24.3%) and (32.5% and 28.9%) in Tanzania and Ethiopia respectively. The prevalence of depression and anxiety found in these studies was far less than in our study conducted during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 98%
“… 23 , 24 Expectedly, pregnant HIV-positive women will have a heightened rate of anxiety and depression. 25 , 26 The current escalating COVID-19 pandemic may worsen this. This study investigated the prevalence of depression and anxiety among pregnant HIV-positive women during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely attributable to 1) decreased treatment compliance in depressed patients; 2) a worsened sense of dyspnea in depressed and anxious patients, which may result in greater hospital admissions; and 3) a sad and/or anxious patient's ability to cope with a chronic disease. On the other hand, cognitive problems are associated with worsening of the disease progression, which leads to an infinity loop until death [139][140][141][142][143][144][145][146][147][148][149]. Considering the severity of the worsened symptoms, the treatment for such brain comorbidities requires further investigations [150].…”
Section: Discussionmentioning
confidence: 99%
“…Existing evidence has suggested that HIV in women in general leads to a range of mental health challenges, including stress, anxiety, depression, sadness and embarrassment [5][6][7][8][9][10]. The stressors for these mental health issues in WLHIV vary and include advanced stage of HIV infection, weakened physical condition, and the fear of a breach of the confidentiality of their HIV status, which may cause further negative impacts on themselves and their family [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%